PEMIKIRAN FIKIH LINGKUNGAN YUSUF AL-QARAḌAWI (Sebuah Upaya Mewujudkan Maṣlaḥah al-’Ammah) (Ahkam: Jurnal Hukum Islam, 2019)
Being one of prominent figures in the field of fiqh, Yusuf al-Qaraá¸awi is one of the contemporary scholars who initiates the ideas and thoughts about fiqh bÄ«Ê»ah (fiqh of environment). The current global environmental crisis ranging from global warming, climate changes, ozone layer depletion, acid rain, exploitation of natural resources, illegal logging, deforestation, floods, droughts, landslides, extinction of biodiversity, and so forth, have been becoming global crucial problems until now. These phenomena become a serious issue since they endanger and threaten the sustainability of the earth. This paper is aimed to study the Islamic perspective on safeguarding the nature and its contents in order to realize maá¹£laá¸¥ah al-â€˜ammah (the public benefits) to the entire population of the earth. The thoughts of Yusuf al-Qaraá¸awi need to be disseminated in order to realize the values of maá¹£laá¸¥ah al-â€˜ammah so that the purpose of realizing Islam as the religion of raá¸¥matan li al-â€˜ÄlamÄ«n (a blessing to all of the universe) may come true.Keywords: Fiqh BÄ«Ê»ah, Jurisprudence of Environment, Maá¹£laá¸¥ah al-â€˜Ammah, Public Benefits